På vej mod short storyen – om søgen efter den litterære identitet i Lise Andersens kortprosasamling "En særlig sommer og andre billeder" (2008) - Zańko, Aldona (Folia Scandinavica Posnaniensia, 2012)
The article derives from the intertextual approach to the notion of literary identity, introduced to the modern literary theory in the 1960’s by Julia Kristeva (born 1941). The main idea behind this approach is that no literary text should be perceived as an isolated unity, but always in relation to other texts, which it refers to. The author applies the intertextual perspective to examine the signs of external literary influences in Lise Andersens minimalist prose collection ”En særlig sommer og andre billeder”, published in 2008. The analysis aims to highlight influences from the American short story genre, which appears as an important source of inspiration not only for Andersen herself, but in fact for most of the Danish writers of minimalist fiction. The analysis provides examples of, how inspiration from the American short story manifests itself in form, narration and structure of the selected stories in the collection. Last but not least, the author draws attention to the general importance of American influences in Danish contemporary short fiction and their role for the critical perception of this literary genre both in Denmark and abroad.